Validitas Media Pembelajaran Interaktif Menggunakan Aplikasi Emaze tentang Materi Protista untuk Peserta Didik SMA - Diah Rahmah Suci; Relsas Yogica; Rahmadhani Fitri; Ganda Hijrah Selaras (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The use of good and appropriate learning media will provide benefits for teachers and students because it can help smooth the teaching and learning process and is very beneficial for students because it can help improve the introduction and understanding of the material being taught. Based on the observations of researchers at SMA Negeri 2 Padang Panjang and interviews with biology teachers, information was obtained that the biology learning media used were Powerpoint, modules, supporting books such as encyclopedias, learning videos from Youtube, and Student Worksheets (LKPD). From the results of the interview, it was revealed that the students had difficulty in understanding the protist material. This type of research is development research using the Instructional Development Institute (IDI) model. The research subjects were two biology lecturers, FMIPA UNP, one teacher and 30 students of class X SMAN 2 Padang Panjang. The object of this research is learning media using the emaze application about protist material for class X students. The research data is the validity data obtained directly through the provision of validity questionnaires to the research subjects. The results showed that the learning media using the emaze application about protist material for class X high school students was very valid with an average validity value of 90.23%. So it can be concluded that the learning media using the emaze application about protist material for class X high school students is very valid